Cumplimiento de pago de la reparación civil fijada a favor del Estado en los juzgados penales de Maynas 2015-2018 - Navarro Ayala, Guiussep (2023)
The content of this Report addresses the study regarding the level of compliance with the payment of the civil reparation set in favor of the State by the jurisdictional bodies of the Superior Court of Justice of Loreto. Likewise, the theoretical framework shows the background, concepts of criminal action, civil action, civil reparation and its legal nature, the principles that guarantee the execution of the judicial sentence, as well as the real coercive measures to promote the payment of civil reparation. The methodology used for the research was the quantitative approach. In the collection of information, documentary analysis was taken into account, while the instrument used was the documentary analysis guide. The evaluation of the results was carried out taking into account the analysis of the content. The main findings discovered have to do with the execution rate of compliance with the payment of civil reparation in judicial processes in which the Peruvian State has the quality of aggrieved party.